STUDIES ON CONCRETE BY PARTIAL REPLACEMENT OF CEMENT WITH VOLCANIC ASH - Susanti, Rika Deni; Tambunan, Ramlan; Waruwu, Aazokhi; Syamsuddin, Munajat (Journal of Applied Engineering Science, 2018)
This paper presents the study on the volcanic ash as replacement of cement on compression strength of concrete. Preliminary study at the early stage were conducted with the specific gravity and sieve analysis of the volcanic as replacement of cement material of concrete. The cement replacement is made with the weight of the volcanic ash in the cement ratio of 2%, 4%, 6%, and 8%. Compressive strength test of concrete was conducted at the age of 7, 14, and 28 days. The mechanical properties by applying slump value and compressive strength were investigated. The result showed that compression strength value of concrete with volcanic ash are close to the same with the normal concrete mix design. The addition of volcanic ash shows improvement of compression strength of concrete.
Keywords: cementation; ashes; volcanics; Strengths; concrete; compressive strength